Artepillin C, a Major Ingredient of Brazilian Propolis, Induces a Pungent Taste by Activating TRPA1 Channels - Hata, Taketoshi; Tazawa, Shigemi; Ohta, Shozo; Rhyu, Mee-Ra; Misaka, Takumi; Ichihara, Kenji (PLOS ONE, 2012)
Brazilian green propolis is a popular health supplement because of its various biological properties. The ethanol extract of Brazilian green propolis (EEBP) is characteristic for its herb-like smell and unique pungent taste. However, the ingredients responsible for its pungency have not yet been identified. This study provides the first evidence that artepillin C is the main pungent ingredient in EEBP and that it potently activates human transient receptor potential ankyrin 1 (TRPA1) channels. EEBP was fractionated using column chromatography with a step gradient elution of an ethanol-water solution, and the fractions having the pungent taste were determined by sensory tests. HPLC analysis revealed that the pungent fraction was composed primarily of artepillin C, a prenylated derivative of cinnamic acid. Artepillin C was also identified as the pungent compound of EEBP by organoleptic examiners. Furthermore, the effects of artepillin C and other cinnamic acids found in EEBP on TRPA1 channels were examined by calcium imaging and plate reader-based assays in human TRPA1-expressing cells to investigate the molecular mechanisms underlying their pungent tastes. Artepillin C and baccharin activated the TRPA1 channel strongly, whereas drupanin caused a slight activation and p-coumaric acid showed no activation. Because the EC50 values of artepillin C, baccharin, and allyl isothiocyanate were 1.8 µM, 15.5 µM, and 6.2 µM, respectively, artepillin C was more potent than the typical TRPA1 agonist allyl isothiocyanate. These findings strongly indicate that artepillin C is the main pungent ingredient in EEBP and stimulates a pungent taste by activating TRPA1 channels.